Responses of phytoplankton and related microbial communities to changes in the limnological conditions of shallow lakes: a short-term cross-transplant experiment - Sinistro, Rodrigo (2015)
We performed a short-term cross-transplant experiment (72 h) using dialysis bags in two shallow lakes with contrasting regimes (clear-vegetated and phytoplankton-turbid). We assessed the changes in the structure of the microbial planktonic communities in response to the variations in the limnological conditions. Important changes were observed in >2 µm-phytoplankton composition in the two transplanted communities (from clear-vegetated to turbid and vice versa). Cyanobacteria biomass (Snowella spp.) increased in the transplanted treatment from the clear to the turbid lake, whereas the contribution of Ochromonas-like sp. diminished. Colonial and filamentous Cyanobacteria species dominated the phytoplankton of the turbid lake throughout the experiment, both in non-transplanted and transplanted waters. Chrysophyceae showed an increasing trend at 72 h in the transplanted treatment (from turbid to clear waters). Heterotrophic bacteria biomass increased in the transplanted treatment from the clear to the turbid system, probably due to a higher availability of more labile sources of dissolved organic carbon (DOC). Our results evidenced changes in the microbial communities in response to important regulator factors (nutrients, light attenuation, DOC availability and top-down control at the microbial food web) in the two contrasting regimes.